Evaluation of Organoleptic Qualities of Fish Grown in Ponds Treated with Different Organic Manures - NANDEESHA, M C; KESHAVANATH, P; UDUPA, K S (Fishery Technology, 2017)
Catla, rohu, silver carp and common carp raised employing different organic manures were subjected to organoleptic evaluation, both in raw and cooked form. The combination treatment of poultry manure and silkworm faecal matter had positive effect on colour and glossiness of skin and colour of flesh in the case of common carp. Though no significant difference was observed in the overall quality, odour of flesh and texture of meat of rohu were found to be better in sewage treated and poultry manure treated ponds respectively. From the results, it can be discerned that treated sewage has no adverse effect on the acceptable qualities of the carps studied.